2013
DOI: 10.1089/gtmb.2012.0229
|View full text |Cite
|
Sign up to set email alerts
|

UCP2 I/D Modulated Change in BMI During a Lifestyle Modification Intervention Study in Japanese Subjects

Abstract: Aim: Polymorphisms in uncoupling protein (UCP) genes have been strongly associated with energy expenditure and obesity. This study aimed at investigating the effects of UCP gene polymorphisms (UCP1 -3826A/G, UCP2A/V, UCP2 I/D, and UCP3 -55C/T) on change in body mass index (BMI) during a lifestyle modification program in Japanese subjects. Results: Intervention induced a significant decrease in energy intake ( -8.6% -17.0%) and a significant increase in energy expenditure (7.7% -7.4%). As a result, participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Moreover, in the human field, some supportive investigations have indicated common mutations on promoter sites of UCP3 are associated with childhood obesity, energy expenditure, body weight alteration, and BMI (Mutombo et al, 2013;Brondani et al, 2014). Almost every research conducted on UCP3 recommended some promotion in feed efficiency and growth performance traits in chicken associated with UCP3 polymorphism in chicken (Nguyen et al, 2015;Moazeni et al, 2016;Jin et al, 2018), in Japanese quail (Murata et al, 2013), in New Zealand Romney lambs (An et al, 2018), and in Angus' steers (Kolath et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in the human field, some supportive investigations have indicated common mutations on promoter sites of UCP3 are associated with childhood obesity, energy expenditure, body weight alteration, and BMI (Mutombo et al, 2013;Brondani et al, 2014). Almost every research conducted on UCP3 recommended some promotion in feed efficiency and growth performance traits in chicken associated with UCP3 polymorphism in chicken (Nguyen et al, 2015;Moazeni et al, 2016;Jin et al, 2018), in Japanese quail (Murata et al, 2013), in New Zealand Romney lambs (An et al, 2018), and in Angus' steers (Kolath et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the vast investigation indicated that this protein may play a major role in body energy expenditure, particularly in skeletal muscle (Bailey et al, 1998;Boss et al, 1998;Raimbault et al, 2001;Abe et al, 2006;Liu et al, 2007). In addition, consecutive pieces of literature were implemented to characterize the gene structure and detect variants in the UCP3, paid particular attention to alteration in energy expenditure, growth, obesity, and body mass index in Human (Mutombo et al, 2013;Brondani et al, 2014;An et al, 2018). Also, UCP3 variation analysis in animal genetic fields, collectively, elucidated significant differentiation on feed efficiency and performance traits in farm animals (Choi et al, 2006;Kolath et al, 2006;Liu et al, 2007;Murata et al, 2013;Moazeni et al, 2016;Jin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies in different populations have veri ed that carriers of the I-allele of UCP-2 gene had a signi cantly higher BMI and promoted possibility of the obesity [27,29]. Besides, it was found that individuals with I/D genotype had an increased rate in basal metabolic, high energy expenditure and lower BMI [30]. Another study revealed that patients with D/D genotype had a remarkable enhancement in total and truncal fat mass and body weight [31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in different populations have veri ed that carriers of the I-allele of the UCP-2 gene had a signi cantly higher BMI and the possibility of obesity [27,29]. Besides, it was found that individuals with I/D genotype had an increased rate of basal metabolism, high energy expenditure, and lower BMI [30]. Another study revealed that patients with D/D genotype had a remarkable enhancement in total and truncal fat mass and body weight [31].…”
Section: Discussionmentioning
confidence: 99%